(untitled) (Advances in Applied Mathematics and Mechanics, 2024)
The sedimentation of a particle cluster with heat and mass transfer is studied with the lattice Boltzmann method. To investigate the effect of thermal convection and mass transfer on the motion of the particle cluster, four cases are studied, namely, without heat and mass transfer, with heat transfer, with mass transfer and with heat and mass transfer. Compared to mass transfer, the effect of thermal convection is more dominant, which affects the motion of the particle cluster significantly. The particle-particle interaction is enforced by thermal convection, and the oscillation of the average settling velocity of the particle cluster is more intense. Besides, with mass transfer between the particles and the fluid, the mass of the particles decreases, the motion of the particles is more sensitive to the fluid flow, the velocity fluctuation of the particle cluster is more intense, the distribution of the particle cluster is more inhomogeneous.